2000
DOI: 10.1080/003655100750046486
|View full text |Cite
|
Sign up to set email alerts
|

QTc interval length and QT dispersion as predictors of mortality in patients with non-insulin-dependent diabetes

Abstract: Patients with non-insulin-dependent diabetes (NIDDM) are at independent risk of cardiovascular death. The reason is only partially understood. The aim of our study was therefore to evaluate the impact of corrected QT interval length (QTc) and QT dispersion (QT-disp) on mortality in a cohort of 324 Caucasian NIDDM patients. A resting 12-lead ECG was recorded at baseline. Maximum (QT-max) and minimum QT (QT-min) intervals were measured, and QT-max was corrected for heart rate (QTc-max). QT-disp was defined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 25 publications
6
70
2
Order By: Relevance
“…In addition to findings of previous reports, we also observed a relation between elevated rHR and both cardiac mortality and mortality due to ischaemic heart disease. On the other hand, the present analysis did not confirm an association between QT c and any of the endpoints in type 2 diabetes as has been reported previously [6,7,9,10,35]. Given previous hypotheses that prolongation of QT c as a marker of cardiac autonomic neuropathy could be of greater importance in type 1 than in type 2 diabetes [5], our findings on this count are intriguing, and it can only be speculated on the underlying mechanisms.…”
Section: Qtc Intervalcontrasting
confidence: 67%
See 2 more Smart Citations
“…In addition to findings of previous reports, we also observed a relation between elevated rHR and both cardiac mortality and mortality due to ischaemic heart disease. On the other hand, the present analysis did not confirm an association between QT c and any of the endpoints in type 2 diabetes as has been reported previously [6,7,9,10,35]. Given previous hypotheses that prolongation of QT c as a marker of cardiac autonomic neuropathy could be of greater importance in type 1 than in type 2 diabetes [5], our findings on this count are intriguing, and it can only be speculated on the underlying mechanisms.…”
Section: Qtc Intervalcontrasting
confidence: 67%
“…Compared with previous publications reporting an association of QT c with mortality in type 2 diabetes [9,10,35], subjects with type 2 diabetes were substantially younger in the present study. It should also be noted that some earlier reports revealing an association between QT c and mortality were cross-sectional [35] or based on a case-control design [9] and in the case of prospective trials [6,7,10] had a considerably shorter follow-up. In type 2 diabetes hyperglycaemia is often associated with a pro-inflammatory state including obesity, dyslipidaemia and hypertension, thereby promoting the development of atherosclerosis [41].…”
Section: Qtc Intervalmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in QT interval corresponds to the fact that, at a cellular level, diabetes lengthens action potentials [24,52] and reduces repolarising of K + currents [52] in a way similar to proarrhythmic medications. QT prolongation predicts mortality in type 1 [53] and type 2 [54][55][56][57][58] diabetes. In the case of type 1 diabetes, QT prolongation conferred an odds ratio for death of 24.6 (95% CI 6.52-92.85) [53].…”
Section: The Two Proarrhythmic Mechanisms and Their Relevance To Hypomentioning
confidence: 99%
“…QT dispersion, which is the difference between the longest and shortest QT interval, is an index of myocardial electrical activity. It was demonstrated that an increase in QT dispersion is associated with the malignant ventricular arrhythmias and sudden death in diabetic patients (Christensen et al 2000).…”
mentioning
confidence: 99%